DALAM PERSPEKTIF EKONOMI, MUNGKINKAH REUNIFIKASI CHINA – TAIWAN DILAKUKAN MELALUI JALAN DAMAI - DIMASTI DANO (KNOWLEDGE: Jurnal Inovasi Hasil Penelitian dan Pengembangan, 2023)
The purpose of this study aims to analyze the influence of China-Taiwan economic relations, United States political relations, and Taiwan's internal factors on the peaceful reunification process. The research was conducted from 1 to 30 December 2022. Data collection techniques were through literature review related to research, including journals, news from social media, and others. In terms of economic perception, the opportunity for the peaceful reunification of China - Taiwan is still open, provided that the economic relations between the two countries can continue to be improved so that they become strong, integrated, and interdependent economic bonds. Learning from the Russia-Ukraine conflict, the military options taken by both sides will lead to the economic destruction" of the two countries simultaneously. But another approach is needed that must be in line especially to attract the majority of Taiwan's population whose status quo supports peaceful reunification. Another strategy is to continue to spur the increase in China's military capabilities to be able to increase the deterrent effect on the United States and its military alliances, with the aim that the United States can refrain from intervening in issues related to reunification. At the same time, China must also be able to refrain from opening conflicts with other countries, especially with countries in the North Natuna sea area. ABSTRAKTujuan penelitian ini bertujuan untuk menganalisa pengaruh hubungan ekonomi China-Taiwan, hubungan politik Amerika Serikat dan faktor dalam negeri Taiwan  terhadap proses reunifikasi damai. Penelitian dilakukan pada 1 sampai dengan 30 Desember 2022. Teknik pengumpulan data melalui kajian pustaka yang terkait dengan penelitian, diantaranya jurnal, berita dari media sosial dan lain-lain. Dalam persepsi ekonomi, peluang reunifikasi damai China – Taiwan masih terbuka, dengan catatan bila hubungan ekonomi ke dua negara dapat terus ditingkatkan sehingga menjadi ikatan ekonomi yang kuat, terintegrasi dan saling ketergantungan. Belajar dari konflik Rusia-Ukraina, opsi militer yang diambil oleh kedua belah pihak akan menyebabkan “kehancuran ekonomi” kedua negara secara bersamaan.Tetapi perlu pendekatan lain yang harus sejalan terutama untuk menarik mayoritas penduduk Taiwan dari status quo menjadi mendukung reunifikasi damai. Strategi lain adalah terus memacu peningkatan kemampuan militer China untuk dapat meningkatkan efek deteren terhadap Amerika Serikat dan aliansi militernya, dengan tujuan agar Amerika Serikat dapat menahan diri untuk tidak turut campur tangan terhadap permasalahan yang terkait reunifikasi. Pada saat yang sama, China juga harus dapat menahan diri untuk tidak membuka konflik dengan negara lain terutama dengan negara-negara di kawasan laut Natuna Utara.